Waste to Wealth: The power of food-waste anaerobic digestion integrated with lactic acid fermentation - Bühlmann, Christopher H.; Mickan, Bede S.; Tait, Stephan; Batstone, Damien J.; Bahri, Parisa A. (Frontiers in Chemical Engineering, 2023)
Food waste (FW) costs the global economy $1 trillion annually and is associated with 8% of anthropogenic greenhouse gas emissions. Anaerobic digestion (AD) is an effective technology for recycling organic waste, including FW, for energy and nutrient recovery.Current major revenue streams for AD include the sale of biogas/power, gate fees, and digestate (fertiliser). However, subsidies provided by governments are a major profit driver for commercial facilities and are generally required for profitability, limiting its widespread adoption. Lactic acid (LA) is a high value intermediate of the AD process and literature evidence has indicated the recovery of LA can significantly boost the revenue generated from FW-AD. Moreover, FW fermentation naturally tends towards LA accumulation, promotion of LA producing bacteria, and inhibition of alternate competing microbes, making LA attractive for commercial production from FW. The integration of LA production and recovery into FW-AD could improve its economic performance and reduce the need for subsidy support, providing a platform for global adoption of the AD technology. However, challenges, such as 1) the low LA yield on FW, 2) seasonality of the FW composition, 3) unknown influence of LA recovery on downstream AD, and 4) impact of standard operational procedures for AD on upstream LA production, still exist making this focus area for future research. Even so, literature has shown the benefits of the LA-AD biorefinery, detailing improved process economics, increased FW utilisation, and elimination of subsidy support. Therefore, this review focuses on exploring the integrating LA production into AD by examining the current status of AD, LA integration strategies, challenges associated with LA production from FW, and identifies key challenges and considerations associated with downstream AD of fermented waste.